Machine Learning-Based Medical Imaging Detection and Diagnostic Assistance - Zeng, Qiang; Sun, Wenjian; Xu, Jingyu; Wan, Weixiang; Pan, Linying (International Journal of Computer Science and Information Technology, 2024)
With the development of medical technology, medical imaging technology plays an increasingly important role in diagnosing and monitoring diseases. At the same time, machine learning technology has shown strong capabilities in data processing and analysis, providing new possibilities for the detection and auxiliary diagnosis of medical images. This paper will deeply discuss the application of machine learning in medical images, especially the application of deep learning in medical images, and how to achieve effective medical image detection and auxiliary diagnosis through steps such as preprocessing, feature extraction, model training and optimization.